Micromorphological intraspecific differentiation of nectar guides and landing platform for pollinators in the Iberian parasitic plant Cistanche phelypæa (Orobanchaceae). Issue 1 (2nd January 2016) - Piwowarczyk, Renata; Carlón, Luis; Kasińska, Justyna; Tofil, Szymon; Furmańczyk, Piotr
Abstract: Holoparasites have evolved a number of adaptations for pollination in parallel with their parasitic strategies. Complex floral pigmentation patterns, comprising spots or stripes that act as visual nectar or landing guides for pollinators, are common and diversified, but their structure and function are poorly understood and almost nothing is known about the role that micromorphological features might play in generating or complementing those visual stimuli. By means of scanning electron and confocal digital microscopy, petal micromorphology was analysed in the two subspecies of the holoparasitic Cistanche phelypæa (subsp. phelypæa and subsp. lutea, Orobanchaceae). Plant material was collected in the semi-deserts of southeastern Spain in 2009 (subsp. lutea ), and in coastal salt marshes in southern Portugal in 2012 (subsp. phelypæa ). Cistanche phelypæa subspecies were already known to differ in several morphological features of flowers and leaves, as well as in their habitats and hosts. Our data have shown that they also differ in several micromorphological features of the petal epidermis. Three different sculpture types of the petal epidermis were recognized. Our results show that petal micromorphology can be used in the separation of taxa, with potential utility in the determination of dried specimens in this genus, inherently poorly preserved in herbaria. The putative influence of the visual and tactile effects originating from this micromorphological variability on the interactions between plants and pollinators and in the reproductive biology of the former is discussed in detail.